Introduksi Spesies Baru Indigofera longeracemosa Boiv. ex Baill. di Puspita Batik Guna Meningkatkan Kualitas Bubuk Pewarna Alami Indigo Melalui Teknologi Convective Drying - Muzzazinah Muzzazinah; Kristiandi Kristiandi; Nurmiyati Nurmiyati; Alanindra Alanindra Saputra (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2021)
This community service partnership program between UNS research group and a small scale batik home industry Puspita Batik located in Bantul, Yogyakarta aims at empowering the small scale batik home industry in producing natural indigo dye. This empowerment program was conducted by: (1) introducing a new indigo plant species to the partner Puspita Batik; (2) cultivating Indigofera longeracemosa for producing indigo dye; (3) improving the quality of indigo natural dye; (4) introducing a convective drying technology for producing indigo dye powder; and (5) widening the target market by developing the website owned by the enterprise. The method used for implementing this program was an action research method, which included discussion, indigo plant nursery and cultivation, production of indigo paste, production of indigo dye powder using convective drying technology, and application of indigo dye powder for producing batik. The first harvest was in August 2021, producing 200 kg indigo leaves, all of which were used to produce 25 kg indigo paste, which was then used to produce 10 kg indigo dye powder. The outcome of this program was an improvement of production capacity of 100%, which was followed by an improvement of sales of 100%. This outcome was due to the output of this program as follows: (1) the cultivation of a new variety of indigo plant; (2) the superior harvest and product quality of Indigofera longeracemosa; (3) a more selling web content and design for marketing; (4) a better way of educating target buyers; and (5) a more effective indigo dye powder packaging which results in low-cost shipping, especially to the buyers abroad.